"THE EFFECT OF CHLOROQUINE ON THE INFECTIVITY OF RODENT MALARIA PARASITES TO ANOPHELES STEPHENSI " - A.N; Hamidi (Tehran University of Medical Sciences, 1977)
There was a statistically significant difference in the number of oocysts, developed in Anopheles stephensi which had fed on mice infected with chloroquine resistant strains (NY 151./2B and. P.y. nigeriensis) and treated with 1 or 10 mg/kg chloroquine phosphate, when compared with the mosquitoes fed on saline injected control animals infected with the same lines. There was no significant difference between the oocyst counts in anophelines that fed on mice which were treated with chloroquine sensitive strains. In the first experiments on rats, with P.y. nigeriensis, greater increase has been shown in oocyst number in mosquitoes fed on dosed rats than in control. In duplicated experiments however, enhancement was approximately double. In chloroquine sensitive strain (ANKA), there was no statistically difference between the numbers, of oocyst developed in chloroquine treated and control rats.